Exposure of calcium carbide induces apoptosis in mammalian fibroblast L929 cells. (24th March 2021) - De, Indranil; S, Rajesh; Kour, Avneet; Wani, Henna; Sharma, Prashant; Panda, Jiban Jyoti; Singh, Manish
Abstract: Inspite of various health warnings from Government and health organizations, Calcium carbide (CaC2 ) is still the most commonly and widely used artificial fruit ripener, probably due to its easy availability, low cost and convenience of usage. Assessment of the hazardous effects of the CaC2 applications for fruit ripening has been a matter of interest since long. Several in vivo studies have reported the toxicological outcomes such as histopathological changes in lungs and kidneys, haematological and immunological responses, upon exposure with CaC2 . However, a well-controlled study investigating the effects of CaC2 under in-vitro setup was lacking. Hence, this study has been conducted to explore the toxicity associated cellular events in L929 cells exposed with varying concentrations of CaC2 (0.00312–0.2 μg/μl) for 24 h exposure time. A 23.14% reduction in cell viability was observed at the highest dose of CaC2 . A similar trend in cellular stress levels at 0.2 μg/μl dose was observed in terms of rounded cellular morphology and decreased adherence as compared to the control. Furthermore, Annexin V FITC/PI staining and subsequent confocal imaging revealed a similar trend of CaC2 induced apoptosis in a dose dependent manner. A gradual elevation of intracellular ROS has also been observed up to 0.025 μg/μl dose. Thus, the study concludes that short term CaC2 exposure may increase the cellular oxidative stress and disturb the redox balance of the cell which then undergoes apoptosis. The study concludes that the exposure of CaC2 can be associated with severe diseases and suggests to stop the uses of CaC2 as fruit ripening agent. Graphical Abstract: